New species and records of Psocoptera (Insecta) from Argentina - Aldrete, Alfonso N. García (Zootaxa, 2009)
From Argentina, one species of Polypsocus and five species of Lachesilla are here described and illustrated, as well as the male of L. corbalanae García Aldrete. New records are presented of 10 species previously not known in this country, also records of three species already known in Argentina. A total of 106 species are now recorded in Argentina.